Pengaruh Faktor-Faktor Motivasi terhadap Kinerja Karyawan (Studi Kasus di Kantor Balai Penelitian Tanaman Kacang-kacangan dan Umbi-Umbian Malang) - Siswanto Wijaya Putra (JAMIN : Jurnal Aplikasi Manajemen dan Inovasi Bisnis, 2020)
The purpose of this study was to to know and analyze how much influence the motivational factors which consist of working conditions, togetherness, rewards, the development of the performance of employees and analyze the motivational factors that have a dominant influence on employee performance Crops Research Institute for Legumes and Tuber Malang. The population in this study as many as 74 people, so the number of population is taken everything for the study, the research done by the census. Mechanical analysis using multiple regression analysis. The analysis showed that motivation which consists of working conditions, togetherness, rewards, development simultaneously affect the performance of employees. Working conditions, and the effect on employee performance rewardss. Togetherness and the development does not affect the performance of employees. Rewards dominant influence on employee performance.